Intercultural sensitivity of greek teachers and relationship with their teaching practice (Research, Society and Development, 2025)
This study aimed to investigate the intercultural sensitivity of Greek primary education teachers and their relationship with their teaching practices. Today, intercultural competence is essential for effective communication and collaboration. Using the Intercultural Sensitivity Scale (ISS) by Chen & Starosta, data was collected, in a social study, from 220 teachers in the Attica region to assess their attitudes toward cultural diversity. The findings indicate that Greek educators exhibit a generally high level of intercultural sensitivity, with strong respect for cultural differences but lower confidence in intercultural interactions. The factors such as age, teaching experience, and migration experience influenced intercultural sensitivity, with younger and less experienced teachers displaying higher levels of engagement and enjoyment in intercultural settings. Additionally, a positive correlation was found between teachers' intercultural sensitivity and their teaching practices, particularly in adapting instruction to diverse student needs. The study underscores the need for targeted intercultural education training to enhance teachers' ability to manage diversity in classrooms. These findings contribute to the broader discourse on intercultural education and highlight the importance of developing culturally responsive teaching approaches.